Research on 3D Measurement and Rapid Location Technique for Assembling the Special-Shaped Structural Segments - Shilei Wang; Zhangming Wang; Qiankuan Feng (Advances in Civil Engineering)
The pylon of the Xinshougang Bridge, a welded steel box arch with a variable cross-section, exhibits asymmetrical design and unevenly inclined limb ends. The segmented assembly of this uniquely shaped steel pylon necessitates precise splicing. In this paper, a novel three-point method for segment attitude positioning is proposed based on the local coordinate system. This method facilitates accurate coordinate translation and attitude alignment between the section preparation facility and the construction site. Furthermore, a predictive methodology for segment posture during erection is introduced, aiming to minimize misalignments at the connection interfaces. This approach accounts for potential deviations arising in manufacturing and erection phases. The synergistic application of these methods effectively ensures the precise geometric shape of the bending and twisting steel tower throughout its phased construction.